MRI-Visible Perivascular Spaces and Risk of Incident Dementia: The Framingham Heart Study. (6th December 2022) - Romero, Jose Rafael; Pinheiro, Adlin; Aparicio, Hugo J.; DeCarli, Charles S.; Demissie, Serkalem; Seshadri, Sudha
Abstract : Background and Objectives: Perivascular spaces (PVS) visible on MRI scans may represent key aspects in the pathophysiology of stroke and dementia, including cerebral small vessel disease and glymphatic dysfunction. This study aimed to determine the association between MRI-visible PVS burden and the risk of incident dementia. Methods: This study included community-dwelling Framingham Heart Study Original and Offspring cohort participants with available brain MRI-PVS ratings, free of stroke and dementia. Multivariable Cox proportional hazard regression was used to obtain hazard ratios (HRs) and 95% CIs of the association between MRI-visible PVS and incident dementia. PVS were rated using validated methods in the basal ganglia (BG) and centrum semiovale (CSO). The outcomes included all-cause dementia, Alzheimer dementia (AD), and vascular dementia (VaD). Results: One thousand four hundred forty-nine participants 50 years or older (46% male) were included. Over a median follow-up period of 8.3 years, the incidence of all-cause dementia, AD, and VaD was 15.8%, 12.5%, and 2.5%, respectively. In models that adjusted for vascular risk factors and cardiovascular disease, the hazard for dementia increased steadily as PVS burden increased, rising 2-fold for those with grade II PVS (HR 2.44, 95% CI 1.51–3.93) to 5-fold in participants with grade IV (HR 5.05, 95% CI 2.75–9.26) compared with grade I PVS in CSO. In the BG, hazards increased 1.6-fold (HR 1.62, 95% CI 1.15–2.27) for grade II to 2.6-fold (HR 2.67, 95% CI 1.04–6.88) for grade IV compared with grade I PVS. The association remained significant for CSO but not for BG, after adjustment for white matter hyperintensity volume (WMHV), covert infarcts, and total brain volume. Similar findings were observed for AD, but VaD, limited by a small number of events, was not statistically significant. Discussion: Higher burden of PVS in CSO was associated with increased risk of developing dementia, independent of vascular risk factors, total brain volume, WMHVs, and covert infarcts. This finding supports a role for PVS as a subclinical MRI marker to identify individuals in subclinical stages at high risk of developing dementia who may benefit from early intervention.